2014
DOI: 10.5539/gjhs.v6n5p284
|View full text |Cite
|
Sign up to set email alerts
|

Neonate Pain Management: What do Nurses Really Know?

Abstract: Purpose:The purpose of this study was to determine knowledge, attitude, and performance vis-à-vis pain management in neonates by nurses working in neonatal units in Bandar Abbas University hospitals.Method:This descriptive and analytical study was executed from March-August 2011 in the neonatal units and NICU in Bandar Abbas educational hospitals. A total of 50 nurses and nurse assistants working in the neonatal units participated in the study. The data collection tool was a structured questionnaire investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
29
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 33 publications
9
29
1
3
Order By: Relevance
“…This knowledge deficit may have an impact on the use of effective and optimal care of a neonate experiencing pain. This finding correlates with other studies, [21,22] which indicated that nurses had poor knowledge of neonatal pain management. In contrast, other studies, [7,12,16,17] reflected higher scores.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This knowledge deficit may have an impact on the use of effective and optimal care of a neonate experiencing pain. This finding correlates with other studies, [21,22] which indicated that nurses had poor knowledge of neonatal pain management. In contrast, other studies, [7,12,16,17] reflected higher scores.…”
Section: Discussionsupporting
confidence: 92%
“…[24] The results indicated that about half of the participants had the right attitude to provide pain management. Almost all participants believed that neonates were able to perceive pain, similar to other studies, [6,20,21] and that comfort measures should always be used. However, most participants believed that analgesia should never or rarely be given, indicating a negative attitude.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Hasil penelitian menunjukkan bahwa BBLR mengalami lebih dari sepuluh prosedur yang menyebabkan nyeri dan ketidaknyamanan selama perawatan di ruang intensif (AsadiNoghabi, Tavassoli-Farahi, Yousefi, & Sadeghi, 2014). Penelitian Beheshtipoor, Memarizadeh, Hashemi, Porarian, dan Rambod (2014) melaporkan sebesar 55-86% prosedur berhubungan dengan pengambilan darah vena.…”
Section: Pendahuluanunclassified